(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Data as well as information is the most valuable tools used for academic effectiveness and for the organization to achieve its aim and objectives. Data is very essential and the cognitive means to collect and organize this data cannot be achieved without human intelligence. In the contemporary society, the means for reliability, accuracy, effectiveness and for a better recognition of an organization has to do with the reliable information and the means to which data can be collected and organized for future use and for the effective management of the organization. Data intelligence guarantees the integral and sustainable development in all aspect of human endeavors; Science and Technologyy, Arts and Humanities and in every other aspect of human development, data intelligence serves as the master key for decision making. This paper critically reviews the necessity of data intelligence and its application areas in harmony with the effectiveness of academic and educational institutions. This work concludes that data intelligence is integral to the effectiveness of any organization including educational institutions and no organizational problem can be tackled without data intelligence. It is recommended that data intelligence should be applied in the Nigeria educational system and machine learning techniques be applied so as to derive meaning from available data banks. This work developed a framework for application of data intelligence in educational system